Analysis of Teacher-Learner Interpersonal Relationship and Learners' Attitudes Towards Biology - Yuliana, Dewi; Zulfiani, Zulfiani (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study explored the interpersonal relationship between teachers' and students' attitudes toward biology. The research method used was a survey, where data were collected from 6 public senior high schools in Depok City, involving 88 grade 11 students selected through cluster random sampling. Two adapted and transliterated questionnaires were employed: the Questionnaire on Teacher Interaction (QTI) and the Test of Science-Related Attitudes (TOSRA). Data was analyzed using Rasch modeling with Winsteps software and other applications such as SPSS and Edraw.AI. The results indicated that the interpersonal relationship between biology teachers and senior high school students in Depok City was relatively positive. Biology teachers were perceived as somewhat dominant but highly cooperative with students in the classroom. On the interpersonal behavior scale, biology teachers exhibited higher leadership, helpful/friendly, and understanding behaviors than opposing behaviors. Furthermore, an analysis of the teachers' interpersonal behavior profiles revealed that biology teachers in Depok City were classified as directive. A two-variable relationship analysis showed a negative correlation between the closeness (CO) dimension, the Attitude Towards Scientific Inquiry dimension, and the influence (DS) dimension with students' career interest in biology.